Prevalence and associated clinical factors for overweight and obesity in young first-episode and drug-naïve Chinese patients with major depressive disorder - Zhang, Jian-Jun; Wang, Xiao-Qian; Zeng, Qun; Gao, Na; Zhang, Xiang-Yang (Frontiers in Psychiatry, 2023)
Background Obesity and overweight are common in young patients with major depressive disorder (MDD). However, the prevalence and associated clinical factors of obesity/overweight in young first-episode and drug-naïve (FEDN) MDD patients are rarely reported in China. Methods A cross-sectional study of 917 young patients (aged 18–35 years) with FEDN MDD was performed. Demographic and clinical data were collected. Depression, anxiety, and psychotic symptoms were assessed using the Hamilton Depression Scale (HAMD), the Hamilton Anxiety Scale (HAMA), and the Positive and Negative Syndrome Scale (PANSS) positive subscale, respectively. Results Among the young MDD patients, the prevalence of obesity and overweight was 4.14 and 52.89%, respectively. Compared to normal-weight patients, overweight patients were older, had a greater age of onset, and had higher TSH and TG levels. Male MDD patients had a higher risk of obesity than female patients. Compared to obese patients, normal-weight and overweight patients had significantly lower HAMD scores, TC levels, and rates of TSH abnormalities. Logistic regression analysis showed that age, age of onset, and sex were independently associated with obesity, and TSH was independently associated with both obesity and overweight, in young MDD patients. Conclusion Our findings suggest a high prevalence of overweight and obesity in young FEDN MDD patients. Several demographic and clinical variables are independently associated with overweight/obesity in these young MDD patients.